Weather and biotic interactions as determinants of seasonal shifts in abundance measured through nest-box occupancy in the Siberian flying squirrel - Vesa Selonen; Kari Hongisto; Mikko Hänninen; Tytti Turkia; Erkki Korpimäki (Nature Research, 2022)
It is much debated whether the direct effects of weather or biotic interactions determine species’ responses to climate change. For example, an important biotic factor for herbivores in northern ecosystems is the availability of winter food. If the food availability changes because of the changing climate, it likely has major impact on the abundance of herbivores. To evaluate this, we need to know the relative roles of weather and biotic interactions, such as food availability and risk of predation, for the species. Here, we utilize long-term data on nest-box occupancy by Siberian flying squirrels (Pteromys volans) in Finland during 2002–2018. We built binary models with nest-box occupancy in different seasons as a response variable. Weather, winter food (tree mast), and predator presence (the Ural owl, Strix uralensis) modified seasonal nest-box occupancy patterns of the flying squirrel. However, the effect of weather was only important in the summer. The negative effect of predators was clear for adults but, surprisingly, not for overwinter survival of apparent juveniles. Considering the relative importance of different factors, winter food availability had a clear positive effect in each season. Our study supports the view that the effects of climate change mediate through multiple biotic interactions. In forest ecosystems, responses of masting trees to weather likely play an important role in species responses to climate change.